2013
DOI: 10.1124/mol.112.082834
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of PI(4,5)P2Synthesis Reveal Dynamic Regulation of IgE Receptor Signaling by Phosphoinositides in RBL Mast Cells

Abstract: Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ) is a versatile phospholipid that participates in many membrane-associated signaling processes. PI(4,5)P 2 production at the plasma membrane (PM) depends on levels of its precursor, phosphatidylinositol 4-phosphate (PI4P), synthesized principally by two intracellular enzymes, PI4-kinases IIIa and IIIb; the former is preferentially inhibited by phenylarsine oxide (PAO). We found that PAO and quercetin, another lipid kinase inhibitor, rapidly inhibit Ca 21 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…We observed parallel inhibition of the stimulated association between oligomeric STIM1 and Orai1, as monitored by fluorescence resonance energy transfer (FRET) between fluorescent protein-tagged constructs [21, 22]. This stimulated FRET was also decreased by 10 μM wortmannin, which inhibits several different phosphoinositide kinases important in Ca 2+ signaling [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed parallel inhibition of the stimulated association between oligomeric STIM1 and Orai1, as monitored by fluorescence resonance energy transfer (FRET) between fluorescent protein-tagged constructs [21, 22]. This stimulated FRET was also decreased by 10 μM wortmannin, which inhibits several different phosphoinositide kinases important in Ca 2+ signaling [23, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we gained distributional information while investigating the effectiveness of inhibitors of PI-kinases in interfering with signaling responses downstream of FcεRI activation in RBL cells. In particular, we observed that re-synthesis of PIP 2 at the plasma membrane following its hydrolysis (stimulated by high concentrations of cytoplasmic Ca 2+ ) occurred in discrete puncta at or near the plasma membrane, as monitored by appearance of PLCδ1 PH-EGF at these sites on the timescale of several minutes at 37°C [24]. These PIP 2 puncta were often as large as several microns in diameter, were stably localized over this time period.The puncta were co-labeled by fluorescent cholera toxin B, often used as a marker for detergent-resistant, ordered membrane domains, similar to previous observations [65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To distinguish whether retention of EGFR in the ER upon PAO treatment is due to phosphatase or PI 4-kinase inhibition, we tested the effects of the PI 4-kinase inhibitors wortmannin and quercetin [2-(3,4-dihydroxy-phenyl)-3,5,7-trihydroxy-4 H -chromen-4-one], neither of which inhibits tyrosine phosphatases at the concentrations used [34,39,40]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, these investigators used 20 mm phenyl arsine oxide (PAO) to inhibit endocytosis of the EGFR. PAO is a potent tyrosine phosphatase inhibitor (Garcia-Morales et al 1990), and also specifically inhibits protein kinase IIa, which is responsible for maintaining the balance of PIP2 in the plasma membrane (Santos et al 2013). PIP2 has been shown to influence the activity of the ErbB1 by binding to the intracellular juxtamembrane domain (Michailidis et al 2011).…”
Section: What Is the Structure Of The Erbb1 In Living Cells?mentioning
confidence: 99%